협력적 팀 접근을 통한 중심반응교수(PRT)가 자폐성장애 유아의 사회적 의사소통 행동에 미치는 영향 - 김설아(Kim, Seol a); 김은경(Kim, Eun kyung) (특수교육논총, 2019)
연구목적: 이 연구에서는 협력적 팀 접근을 통한 중심반응교수(PRT)가 자폐성 장애 유아의 사회적 의사소통 행동에 미치는 영향을 알아보았다. 연구방법: 연구대상은 자폐성 장애 유아 2명이었다. 연구 설계는 대상자간 중다 간헐 기초선 설계를 적용하였으며, 기초선, 중재, 유지, 일반화 순서로 진행하였다. 중재는 대상 유아가 다니고 있는 사설 치료실에서 실시하였다. 연구결과: 협력적 팀 접근을 통한 중심반응교수(PRT)가 자폐성장애 유아의 사회적 의사소통 행동 증가에 효과적인 것으로 나타났다. 중재의 효과는 중재가 종료된 후에도 유지 되었으며, 다른 대상과 상황에서도 중재 효과가 일반화 되었다. 이 연구의 결과는 자폐성장애 유아의 사회적 의사소통 행동을 증가시키기 위한 협력적 팀접근을 통한 중심반응교수(PRT)가 효과적임을 시사한다. 결론: 이 연구는 치료지원 현장에서 가장 쉽게 적용 가능한 협력적 팀 접근 형태로, 자페성장애 유아의 교육적 성취를 위해 센터 내 감각통합치료사와 언어치료사가 책임을 공유 하면서, 각자의 전문적 분야에서 교육적 효과를 극대화시키기 위한 협력적 팀 접근을 실시하였다는 데 의의가 있다. Purpose: The purpose of this study was to investigate the effect of Pivotal Response Teaching(PRT) through collaborative team approach on the social communication behavior of children with autism spectrum disorders. Method: The subjects were two autism spectrum children. The study design was applied to multiple probe across participants and the baseline, intervention, maintenance, and generalization were performed. The intervention was conducted in the treatment room where the children were attending. Results: The results of this study showed that PRT, through collaborative team approach, was effective in increasing social communication behaviors of autism spectrum disorders. The intervention effect was maintained after the intervention was terminated, and the mediation effect was generalized in other subjects and situations. Conclusion: The results of this study suggest that the pivotal response teaching through collaborative team approach to increase the social communication behavior of childern with autism spectrum disorders is effective. The intervention effect was maintained even after the intervention ended. The results of this study suggest that intervention combining discrete trial treatment and pivotal response treatment to increase social communicative behavior of children with autism spectrum disorders is effective. KCI Citation Count: 2